TEACHER TRAINING ITINERARIES: FROM THE SUBWAY STATION TO THE PAVING OF THE DREAM OF BEING A TEACHER - de Alencar, Kalleu; de Assis Francelino Alves, Francisco (Revista Gênero e Interdisciplinaridade, 2023)
The profession of teaching is something dedicated to teaching. For some, it becomes a priesthood, necessary to be born with the proper “gift” for the teaching profession, being considered an ancient function, permeated by all the millennia of humanity. In view of this, it is commonly questioned about the obstacles and bad weather of the profession. The present work deals with the itineraries of teacher training, a discussion about the daily transfer carried out by academics of the Higher Degree in Chemistry at the Federal Institute of Ceará - IFCE Campus Maracanaú, coming from Maranguape, Caucaia, Pacatuba, Fortaleza, and even Horizonte , bringing the confrontations that the respective students face in order to fulfill the “dream” of teaching, of completing their higher education and obtaining a diploma. For this, a questionnaire was applied to 10 students of the course, between the ages of 18 and 25 years, consisting of 10 subjective items that sought to identify the perception of the researched subjects about the difficulties of access and locomotion to the educational institution. As a result, we obtained varied responses from academics regarding the difficulties, but in all, the same link was observed, in which they report on how the focus of completing the graduation and the pleasure of the act of teaching bring motivation and make such ailments ridiculous, when compared with the aligned perspectives of these teachers in training. In short, we concluded the research having the objectives outlined being achieved.